-3k+2k+5k+9=-7

Simple and best practice solution for -3k+2k+5k+9=-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3k+2k+5k+9=-7 equation:


Simplifying
-3k + 2k + 5k + 9 = -7

Reorder the terms:
9 + -3k + 2k + 5k = -7

Combine like terms: -3k + 2k = -1k
9 + -1k + 5k = -7

Combine like terms: -1k + 5k = 4k
9 + 4k = -7

Solving
9 + 4k = -7

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 4k = -7 + -9

Combine like terms: 9 + -9 = 0
0 + 4k = -7 + -9
4k = -7 + -9

Combine like terms: -7 + -9 = -16
4k = -16

Divide each side by '4'.
k = -4

Simplifying
k = -4

See similar equations:

| 2/5m=7/10m=2/7/1/4 | | 2x+4/4=x-8/3 | | z^(2/3)-2z^(1/3)=15 | | fx=5x-1 | | -2y+3w=10 | | 24/y=8/3 | | 4x+5+2x+8= | | 4x-2y-3x+5y= | | 7x^2+20x-18=0 | | 2x+6(-2.5x+5)=-4 | | (-2)x(-25)= | | x+x*x=16 | | -46=3x+7y | | x/9-5/6=4x/9 | | (X-17.7)+19.6=28.8 | | 3-2a=15 | | 7(10x+8)=-364 | | 4y+4-3y=2y-6 | | f(x)=4x^2+6x+3 | | r/3-3/8/r=-3/4 | | 6y+2(3x+5)+2y+3= | | 5(x-3)=4x-9+3x | | 5a+b=2 | | (5.6*10^-6)/(7*10^3)= | | -7x-4(5x-2)=197 | | 3x-3(x+1)=e | | 5.6*10^-6/7*10^3= | | 14x-17=6x-10 | | 5.6X10^-6/7X10^3= | | h^2+9h+8=0 | | sin^2xcos^2x=1-cos4x/8 | | 5(a-2)=3(a+1) |

Equations solver categories